Immaterial Compensation Not Criminal Losing Lives as an Implementation of Victim Protection - Tommy Tommy; Febrian Febrian; Nashriana Nashriana; Ruben Achmad (Universitas Lampung, 2022)
Immaterial compensation is compensation that cannot be calculated with money, such as pain, loss, and psychic, but the compensation can be replaced with some money. The existence of immaterial compensation aims to protect victims of loss of life from other people such as children and wives, families, and parents. Based on the Criminal Code, hereinafter referred to as the Criminal Code, the regulation of the crime of taking life is regulated in Articles 338 to 340. The most severe threat of punishment is contained in Article 340 of the Criminal Code, namely the death penalty, or can be said to be life imprisonment, or for a while. certain period, with a maximum period of 20 (twenty) years. Therefore, the existence of liability for compensation from the defendant to the victim can reduce the defendant's sentence or can replace the main sentence of the defendant.T he research method uses a type of qualitative research sourced from the various scientific literature.